Peran Pupuk Organik dalam Peningkatan Efisiensi Pupuk Anorganik pada Padi Sawah (Oryza sativa L.) - Siwanto, Totong; ,, Sugiyanta; Melati, Maya (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 2015)
ABSTRACTApplication of organic fertilizer into the soil is designated as a source of macro, micro nutrients and organic acids; it also acts as soil ameliorant that improve physical, chemical and biological properties of soil. Application of high rates organic fertilizer has a constraint namely the availability and ease of application. Therefore, it is necessary to learn the use of organic fertilizer with low rates to improve the efficiency of chemical fertilizers. This research was aimed to study the effect of organic and inorganic fertilizers on growth and yield of paddy rice, as well as the efficiency of N, P, K inorganic fertilizer. Field experiment was conducted at Sawah Baru Research Station, University Farm IPB, Bogor, West Java from September to December 2013. The experiment used Randomized Block Design consisted of two factors: rates of organic fertilizer (0, 250, 500, 750, and 1,000 kg ha-1), and rates of inorganic fertilizer (0, 100, 200, 300, and 400 kg ha-1). The results suggested that the application of 1,000 kg organic fertilizer ha-1 + 400 kg inorganic fertilizer ha-1 did not show significant interaction. Application of organic fertilizer alone up to 1,000 kg ha-1 resulted in low growth and yield. Increasing rates of  application up to 400 kg inorganic fertilizer ha-1 increased the growth and yield of paddy rice. The highest N efficiency was 89.19% at a rate of 500 kg organic fertilizer ha-1 + 200 kg inorganic fertilizer ha-1, whereas the highest efficiency of P and K, respectively were 69.55% and 92.52% at a rate of 750 kg organic fertilizer ha-1 + 300 kg inorganic fertilizer ha-1.Keywords: NPK, organic fertilizer, paddy rice